2020
DOI: 10.1111/camh.12427
|View full text |Cite
|
Sign up to set email alerts
|

Debate: Student mental health matters – the heightened need for school‐based mental health in the era of COVID‐19

Abstract: Child and adolescent psychiatrists are taught from day 1 of training to always place the child's best interest first. However, children can only do well when their caregivers and communities are similarly well supported. In considering the complex challenges of the COVID-19 crisis, the best interests of children can only be met by simultaneously considering the best interests of parents, families, teachers, and school staff. As schools open, in whatever shape or form, mental health practitioners who work in sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 2 publications
0
10
0
3
Order By: Relevance
“…These limitations notwithstanding, our findings have implications for supporting families with SEN. Our study showed that poor mental health was an important risk factor of the wellbeing of children with SEN during the pandemic. Mental health lay the foundation from which children and young people can start exploring the learning opportunities available to them (Weisbrot and Ryst, 2020). Therefore, the aims of education post-pandemic should be re-examined and consider the systematic implementation of school-wide and selective evidence-based intervention programs to support the outcomes of children with SEN.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations notwithstanding, our findings have implications for supporting families with SEN. Our study showed that poor mental health was an important risk factor of the wellbeing of children with SEN during the pandemic. Mental health lay the foundation from which children and young people can start exploring the learning opportunities available to them (Weisbrot and Ryst, 2020). Therefore, the aims of education post-pandemic should be re-examined and consider the systematic implementation of school-wide and selective evidence-based intervention programs to support the outcomes of children with SEN.…”
Section: Discussionmentioning
confidence: 99%
“…A prevenção da ansiedade em adolescentes frente à pandemia por COVID-19 vem ganhando cada vez mais espaço na literatura. Psiquiatras, pediatras e provedores de cuidados primários precisam estar atentos à saúde mental da população de adolescentes, especialmente com ênfase aos sintomas de ansiedade nessa parcela da população e, nesse sentido, intervenções práticas e psicológicas bem estabelecidas podem ajudar a prevenir a ansiedade em adolescentes no contexto de isolamento social durante a pandemia de COVID-19 (Weisbrot, 2020).…”
Section: Prevenção Da Ansiedade Em Adolescente Frente à Pandemia Por Covid-19unclassified
“…Manter um estilo de vida saudável com contatos sociais e informações sobre onde obter tratamento médico, se necessário, parecem auxiliar os adolescentes a enfrentar melhor as situações e prevenir a ansiedade que possa surgir (Weisbrot, 2020). Courtney (2020) destaca a preponderância em atentar à saúde mental de adolescentes com depressão e ansiedade preexistentes; além de otimizar a intervenção para prevenir os efeitos negativos.…”
Section: Prevenção Da Ansiedade Em Adolescente Frente à Pandemia Por Covid-19unclassified
See 1 more Smart Citation
“…Schools continue to become a critical piece of the mental health system for children and adolescents (Hoover & Bostic, 2020 ). As noted by Weisbrot and Ryst ( 2020 ), the COVID-19 pandemic only intensified the need for mental health supports in schools for students as well as faculty and staff within school settings. To meet these needs, comprehensive systems are needed within schools, which include both school personnel (e.g., educators, school psychologists, social workers, etc.)…”
mentioning
confidence: 99%